Confucius Institute to be set up in UMP - Pejabat, Naib Canselor UMP (Pejabat Naib Canselor, 2018)
Universiti Malaysia Pahang (UMP) has entered into an agreement with Confucius Institute Headquarters (Hanban) that would pave the way for the establishment of Confucius Institute or Kong Zi Institute in Pahang.